Which rule describes the relationship between the input and output pairs in the following table?Input

Which rule describes the relationship between the input and output pairs in the following table? Input Output
555 101010
101010 202020
151515 303030
Choose 1
Choose 1

(Choice A)
A
Add 101010 to the input to get the output.

(Choice B)
B
Multiply the input by 222 to get the output.

(Choice C)
C
Multiply the input by 333. Then subtract 555 from the result to get the output.

Related Posts

This Post Has 7 Comments

  1. 1. d. d = 66t

    The maximum speed of the wildebeest is v=66 ft/s. Speed is defined as the ratio between the distance covered (d) and the time taken (t):

    [tex]v=\frac{d}{t}[/tex]

    Re-arranging the formula, we get

    [tex]d=vt[/tex]

    And substituting v=66 ft/s, we find

    [tex]d=66t[/tex]

    2. c. y = 5 - n

    In fact, we can check that this rule satisfies all the numbers of the sequence:

    n=3 --> y = 5 - 3 = 2

    n=4 --> y = 5 - 4 = 1

    n=5 --> y = 5 - 5 = 0

    n=6 --> y = 5 - 6 = -1

    3. d. $5.50, $11.00, $16.50; E = 5.50h

    In fact, if we use the rule E=5.50 h, we see that the table is completed as follows:

    h=1 --> E=(5.50)(1 h)=5.50$

    h=2 --> E=(5.50)(2 h)=11.00 $

    h=3 --> E=(5.50)(3 h)=16.50$

    h=4 --> E=(5.50)(4 h)=22.00$

    h=5 --> E=(5.50)(5 h)=27.50$

    4. c. if d ≥ 5 then C = 4.70d, if d < 5 then C = 4.70d - 1; $17.80, $32.90

    If the number of days is more than 5, the cost is 4.70$ per day, therefore c=4.70d (where d is the number of days); if the number of days is less than 5, one dollar is returned, so the cost will be C=4.70d-1. By applying this rule, we can calculate the rental cost after d=4 days and d=7 days:

    - d=4 --> c=4.70*4-1=17.80$

    - d=7 --> c=4.70*7=32.90$

    5. b. y = 3x + 3

    In fact, we can check this is the correct rule by substituting the numbers:

    x=0 --> y=3*0+3=3

    x=1 --> y=3*1+3=6

    x=2 --> y=3*2+3=9

    x=3 --> y=3*3+3=12

    x=4 --> y=3*4+3=15

    7. x -2 -1 0 1 2

    y (-16 ) (-6 ) (4 ) (14 ) (24 )

    The rule we have to apply is:

    -10x + y = 4

    Re-arranging it, we can solve for y:

    y = 10x + 4

    So, let's substitute the different values of x:

    x=-2 --> 10*(-2)+4=-20+4= -16

    x=-1 --> 10*(-1)+4=-10+4= -6

    x=0 --> 10*0+4= 4

    x=1 --> 10*1+4=10+4= 14

    x=2 --> 10*2 +4 =20+4 = 24

    8. y = -5x - 1

    In fact, if substitute the different values of x given by the problem, we find:

    x = -2 --> y = -5*(-2) -1= 10 -1 = 9

    x = -1 --> y = -5*(-1) -1 = 5 -1 = 4

    x = 0 --> y = -5*0 -1 = -1

    x = 1 --> y = -5*1 - 1 = -6

    x = 2 --> y = -5*2 -1 = -11

Leave a Reply

Your email address will not be published. Required fields are marked *